Assessmentof the Wastewater Treatment System at VPC Printing and Packaging Joint Stock Company - Ngoc Binh, Hoang; Hong, Tran Thi (VNU Journal of Science: Earth and Environmental Sciences, 2025)
Wastewater of VPC Printing and Packaging Joint Stock Company includes domestic wastewater of workers and paper production wastewater, containing many suspended solids and organic compounds which can be hazardous waste for the environment and public health. Research results show that the wastewater treatment system at VPC Printing and Packaging Joint Stock Company has applied chemical-physical treatment technology combined with biological treatment, with a treatment capacity of 20 m 3 /day.night. The system is currently operating stably, in which water quality parameters including pH, BOD 5 , COD, TSS, and color after treatment meet the discharge requirements according to QCTĐHN 02:2014/BTNMT and QCVN 12-MT:2015/BTNMT standards. Further studies are needed to improve the system to enhance the efficiency of treating organic compounds that are difficult to decompose.